2022
DOI: 10.1177/20552076221102261
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of people and family carers from under-represented groups in self-managing Parkinson's disease and their use of digital health to do this

Abstract: Introduction Digital health is thought to enable people to better manage chronic conditions, such as Parkinson's. However, little is known about how people from under-represented groups with chronic conditions use digital health to self-manage. Objective The objective of our study was to explore the experiences of people and family carers from under-represented groups in self-managing Parkinson's, including their use of digital health to do this. Methods Semi-structured interviews (n = 18, including four dyadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Obtaining health‐related information relies on adequate health literacy but as the development of digital health services grows, the skillset required for accessing such services becomes more complex, 32 creating an even greater need for effective strategies of support. The ability to process information and engage in digital services as well as having access to technology are some of the key domains necessary to use digital health resources; a deficit in any area can cause health inequalities 33 . Low digital literacy amongst participants revealed challenges around self‐management due to limited digital skills/education and limited access to digital resources because of financial restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obtaining health‐related information relies on adequate health literacy but as the development of digital health services grows, the skillset required for accessing such services becomes more complex, 32 creating an even greater need for effective strategies of support. The ability to process information and engage in digital services as well as having access to technology are some of the key domains necessary to use digital health resources; a deficit in any area can cause health inequalities 33 . Low digital literacy amongst participants revealed challenges around self‐management due to limited digital skills/education and limited access to digital resources because of financial restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to process information and engage in digital services as well as having access to technology are some of the key domains necessary to use digital health resources; a deficit in any area can cause health inequalities. 33 Low digital literacy amongst participants revealed challenges around self‐management due to limited digital skills/education and limited access to digital resources because of financial restrictions. Difficulties (including financial restrictions) in accessing digital/electronic health information intersect with experiences of low health and financial literacy, but also with ethnicity since participants from minority ethnic backgrounds were evidenced as less technologically able to self‐educate or access health apps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the complexity and diversity of the needs of older people with frailty, some face inequities in access to interventions which may help to maintain or improve their independence. 3 For example, while telemedicine can beneficial, cost-effective and acceptable to older people, 13 there are concerns about digital exclusion 14 and risks that important signs and symptoms could be missed. 15 Improving the effectiveness and efficiency of CGA 11 requires exploration of how individual components may work and how the overall intervention can be enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that an operational definition of self-management is needed as this can heavily influence the records review on such interventions, this might also be true when reviewing self-efficacy interventions due to their shared complexity 21. Earlier reviews which have explored self-management interventions for PwP from qualitative and quantitative perspectives have not examined digital interventions which promote self-efficacy in PwP 4 8 22 23…”
Section: Introductionmentioning
confidence: 99%